Vascular Smooth Muscle Cells Inhibit the Plasminogen Activators Secreted by Endothelial Cells - Laug, Walter E (Thrombosis and Haemostasis, 1985)
TPure cultures of bovine endothelial cells (EC) produce and secrete large amounts of plasminogen activators (PA). Cocultivation of EC with vascular smooth muscle cells (SMC) resulted in a significant decrease of PA activities secreted by the EC, whereas the cellular PA activities remained unaffected. Secreted PA activities were absent in the growth medium as long as the SMC to EC ratio was 2:1 or higher. The PA inhibitory activity of the SMC was rapid and cell-to-cell contact was not necessary.The PA inhibitory activity was present in homogenates of SMC as well as in the medium conditioned by them but not in the extracellular matrix elaborated by these cells. Serum free medium conditioned by SMC neutralized both tissue type (t-PA) and urokinase like (u-PA) plasminogen activators. Gel electrophoretic analysis of SMC conditioned medium followed by reverse fibrin autography demonstrated PA inhibitory activities in the molecular weight (Mr) range of 50,000 to 52,000 similar to those present in media conditioned by bovine endothelial cells or fibroblasts. Regular fibrin zymography of SMC conditioned medium incubated with u-PA or t-PA revealed the presence of a component with a calculated approximate Mr of 45,000 to 50,000 which formed SDS resistant complexes with both types of PA.These data demonstrate that vascular SMC produce and secrete (a) inhibitor(s) of PAs which may influence the fibrinolytic potential of EC.
Keywords: Endothelial cells; Vascular smooth muscle cells; Inhibitors of plasminogen activators